Impact of COVID-19 on patients with rheumatic complications of cancer immunotherapy: results of a registry survey - Anne R Bass; Karmela K Chan; Nilasha Ghosh; Aidan Tirpack (Journal for ImmunoTherapy of Cancer)
Immune checkpoint inhibitors (ICI) block negative regulatory molecules, such as CTLA-4, PD-1 and PD-L1, in order to mount an antitumor response. T cells are important for antiviral defense, but it is not known whether patients with cancer treated with ICI are more or less vulnerable to viral infections such as COVID-19. Furthermore, immunosuppressive treatment of immune-related adverse events (irAE) may also impact infection risk. Rheumatic irAEs are often persistent, and can require long-term treatment with immunosuppressive agents. The aim of this study was to determine the incidence of COVID-19 infection and assess changes in ICI and immunosuppressive medication use among patients enrolled in a prospective rheumatic irAE registry during the height of the COVID-19 pandemic. On April 16 2020, following the ‘surge’ of COVID-19 infections in the New York Tri-State area, we sent a 23-question survey to 88 living patients enrolled in a single institutional registry of patients with rheumatic irAE. Questions addressed current cancer and rheumatic irAE status, ICI and immunosuppressant medication use, history of COVID-19 symptoms and/or diagnosed infection. A follow-up survey was sent out 6 weeks later. Sixty-five (74%) patients completed the survey. Mean age was 63 years, 59% were female, 70% had received anti-PD-(L)1 monotherapy and 80% had had an irAE affecting their joints. Six patients (10%) had definite or probable COVID-19, but all recovered uneventfully, including two still on ICI and on low-to-moderate dose prednisone. Of the 25 on ICI within the last 6 months, seven (28%) had their ICI held due to the pandemic. In patients on immunosuppression for irAE, none had changes made to those medications as a result of the pandemic. The incidence of COVID-19 was no higher in patients still on ICI. Ten percent of rheumatic irAE patients developed COVID-19 during the NY Tri-state ‘surge’ of March–April 2020. Oncologists held ICI in a quarter of the patients still on them, particularly women, those on anti-PD-(L)1 monotherapy, and those who had had a good cancer response. The incidence of COVID-19 was no higher on patients still on ICI. None of the patients on disease-modifying antirheumatic drugs or biological immunosuppressive medications developed COVID-19.